Advances in nanoparticle‐based lateral flow immunoassay for point‐of‐care testing. Issue 1 (31st January 2022) - Lou, Doudou; Fan, Lin; Jiang, Tao; Zhang, Yu
Abstract: As a representative technology for point‐of‐care testing (POCT), lateral flow immunoassay (LFIA) has been broadly used to detect analytes in many fields. However, its clinical application is severely limited by the unsatisfactory sensitivity, which makes it difficult to obtain accurate results when detecting biomarkers of trace levels, especially in complex matrices. Nanoparticles have been introduced into LFIA for years and become an indispensable part, acting not only as carriers that load and enrich biomolecules, such as antibodies and dyes, but also a miniature platform applied for creative design and construction of nanoprobes. Due to the unique properties at the nanoscale, including the mimetic enzyme activity, the characteristic plasma resonance spectrum and so on, nanomaterials exhibit great potential in the development of novel LFIA and high‐sensitivity detection. Abstract : Lateral flow immunoassay (LFIA) is a representative point‐of‐care testing (POCT) technology, but its clinical application of LFIA is severely limited due to the unsatisfactory sensitivity. Nanoparticles used in LFIA act not only as carriers that load and enrich biomolecules, such as antibodies and dyes, but also a miniature platform applied for creative design and construction of nanoprobes. In this mini‐review, the authors introduce their unique properties at the nanoscale including the mimetic enzyme activity, the characteristic plasma resonance spectrum, and so on, and their multiple functions in the development of novel LFIA and high‐sensitivity detection.